2010
DOI: 10.1109/tuffc.2010.1559
|View full text |Cite
|
Sign up to set email alerts
|

Guided wave diffraction tomography within the born approximation

Abstract: Detection and sizing of corrosion in pipelines and pressure vessels over large, partially accessible areas is of growing interest in the petrochemical industry. Low-frequency guided wave diffraction tomography is a potentially attractive technique to rapidly evaluate the thickness of large sections of partially accessible structures. Finite element simulations of a 64-element circular array on a plate show that when the scattering mechanism of the object to be reconstructed satisfies the Born approximation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 25 publications
2
103
0
Order By: Relevance
“…O b can be obtained from the ray tomography reconstruction, and equation (2.14) can be rewritten as 19) where p b and G b are estimates of the incident wavefield and Green's functions, respectively, in the background O b ; complete details of how they are calculated are in [21]. As before, this forms a linearization, provided p b and G b remain constant, which enables O δ to be calculated directly.…”
Section: (Iii) Harbutmentioning
confidence: 99%
See 1 more Smart Citation
“…O b can be obtained from the ray tomography reconstruction, and equation (2.14) can be rewritten as 19) where p b and G b are estimates of the incident wavefield and Green's functions, respectively, in the background O b ; complete details of how they are calculated are in [21]. As before, this forms a linearization, provided p b and G b remain constant, which enables O δ to be calculated directly.…”
Section: (Iii) Harbutmentioning
confidence: 99%
“…For this, a piezoelectric transducer was used to excite the A 0 wave; this transducer is as described in [19]. This is around 10 mm in diameter (i.e.…”
Section: (E) Experimental Validationmentioning
confidence: 99%
“…The study showed that Lamb wave diffraction tomography could further improve image quality and resolution. Belanger et al (2010) proposed a time-of-flight diffraction tomography within the Born approximation using low frequency Lamb waves. Their study employed a transducer network with 64 transducers to evaluate reduction in plate thickness.…”
Section: Background Of the Proposed Methodsmentioning
confidence: 99%
“…As shown in the dispersion curves of figure 1, the guided wave velocity is a function of the frequency-thickness product, so by fixing frequency, wave velocity can be shown to be a function of thickness. This is a widely used assumption which has been used for 20 years in guided wave tomography [3][4][5][6][7][8][9][10][11][12] but relies on a key approximation. The dispersion curves are derived for infinite plates of constant thickness [13]; therefore, the assumption is made that any local thickness variations are sufficiently gradual that they can be neglected.…”
Section: Introductionmentioning
confidence: 99%